GRB2, a protein known for a long time with a new autophagy-regulating function - Silvia Vega-Rubin-de-Celis (Autophagy Reports)
BECN1 (BCL2 interacting myosin like coiled protein) is a major regulator of autophagy and a haploinsufficient tumor suppressor. BECN1 binds to multiple proteins and it is part of at least two different class III phosphatidylinositol (PI) 3 Kinase (PI3KC3) complexes that regulate autophagy and endocytic trafficking through the biosynthesis of phosphatidylinositol-3-phosphate. BECN1 and the activity of the PI3KC3 are regulated by post-translational modifications and/or subcellular localization. We recently discovered that GRB2 (growth factor receptor bound protein 2), an adaptor protein of several tyrosine kinases, interacts with BECN1 and regulates autophagy.1